Comparative Study: Biguanide-, Sulfonamide-, and Natural Agent-Based Interventions in an In Vivo Experimental Diabetes Model - Iulian Tătaru; Ioannis Gardikiotis; Carmen Lidia Chiţescu; Oana-Maria Dragostin; Maria Dragan; Cerasela Gîrd; Alexandra-Simona Zamfir; Simona Iacob (Ciobotaru); Rodica Vatcu; Catalina Daniela Stan; Carmen Lăcrămioara Zamfir (Medicina)
Background/Objectives: In the context of diabetes, a multifactorial metabolic disorder with significant clinical implications, the present study investigates the hypoglycemic effects of a synthetic sulfonamide (S) administered individually and in combination with Salvia officinalis extract, compared to metformin as a standard therapeutic agent. Methods: An in vivo model of experimentally induced diabetes using alloxan was applied to Wistar female rats, divided into six experimental groups, including a healthy control group and a diabetes-induced, untreated group. Plasma concentrations of metformin and sulfonamide were quantified by high-performance liquid chromatography. The plasma steady-state concentrations of the pharmaceutical agents and their correlation with hypoglycemic effect were evaluated. Results: The combination of the synthetic sulfonamide (S) with Salvia officinalis extract resulted in the greatest reduction in blood glucose level (average value of 50.2%) compared to S (40.6%) or metformin (36.4%). All treatments demonstrated statistically significant differences in blood glucose levels compared to the diabetes-induced untreated group (p < 0.05). Pharmacokinetic analysis revealed a larger volume of distribution for the synthetic sulfonamide S (23.92 ± 8.40 L) compared to metformin (16.07 ± 5.60 L), consistent with its physicochemical properties. No significant correlation was found between plasma drug levels and glycemic response (p > 0.05). Conclusions: Our findings support the potential of combining standard therapeutic agents with natural alternatives such as Salvia officinalis to achieve improved glycemic control through complementary mechanisms. To the best of our knowledge, this is the first in vivo study to evaluate the combined effects of a sulfonylurea-type compound and Salvia officinalis extract in a diabetic animal model.